Mount Ucka and the shrine of our Lady of Trsat - Ceruti, María Constanza (2020)
The relationship between the Croatian massif known as Mount Ucka, Slavic mythology, tourism and popular religiosity in northern Croatia is addressed in this paper. For this, informal interviews and anthropological field observations are carried out on the buttresses and the summit of Vojak Peak, in the Poclón mountain refuge, in the villages of Veprinac and Volosco; and in the sanctuary of Trsat, an important place of pilgrimage and popular Christian devotion, located on a hill near Mount Ucka. In addition, the symbolic construction of the sacred mountain and its importance in strengthening the Croatian identity are analyzed, taking into account the recreation of Slavic mythology through its representation in the tourist brochures of the Opatija Riviera. Also, for comparative purposes for the present investigation, other sacred mountains in Croatia such as Mount Vidova Gora on the island of Brac or the Biokovo massif in Makarska were ascended. Mount Ucka participates in the universality of the myth of the struggle between celestial deities and the underworld, through the figure of Perún, the Slavic atmospheric god, whose dwelling is identified with one of the coastal buttresses of the massif. Other mythological entities, such as the witches who inhabit the karst pinnacles, or the so-called Babbo Natale, refer to the mountain folklore characteristic of Eastern Europe and the east of the Alpine arch. The process of Christianization of this mountain is reflected in the local toponymy and in the dispersion of churches, Marian sanctuaries and abbeys. The investigation was completed with an ascent to the hill of Trsat, to document the activity of the pilgrims in the church and the offerings deposited in the votive chapel. The oldest Marian shrine in Croatia is located on a small elevation on the other side of the Kvarner Gulf, which offers a privileged view of the Ucka massif and the Abbey riviera.